Identification of a Nuclear Localization Signal (NLS) in Human Transcription Elongation Factor ELL2 - Kohrt, Stephan; Baheerathan, Abarna; Prokscha, Jonas; Zwosta, Alexandra; Sticht, Heinrich; Thoma-Kreß, Andrea (Cell Biochemistry and Function, 2024)
ELL2 is a transcription elongation factor suppressing transcriptional pausing of RNA polymerase II, thereby enhancing gene expression. In accordance with the nuclear localization of ELL2, the protein is supposed to carry out its function in promoting transcription in the nucleus. Yet, it is unknown whether ELL2 carries a nuclear localization signal (NLS). In this study, we identify the NLS of ELL2. In silico analysis resulted in prediction of a strong bipartite NLS with an exceptionally high score at amino acids 311–338 in the conserved region R1 of ELL2. Confocal laser scanning microscopy of a series of ELL2 truncation mutants and quantitative analysis of images verified the presence of R1 to be decisive for nuclear localization of ELL2 suggesting that the predicted NLS is accurate. Deletion of key basic amino acids within the putative NLS in silico and in vitro showed that K319, R320, and K333/K334 are crucial for ELL2's nuclear accumulation, thus confirming the predictions. The isolated ELL2-NLS was able to translocate an unrelated NLS-mapping system into the nucleus underlining the strength of the NLS. Taken together, we identified the NLS of ELL2 and mapped individual aa that are crucial for nuclear localization of ELL2.
CRIS-Team Scopus Importer:2024-12-13
Keywords: ELL2; NLS; nuclear localization signal; transcription elongation factor

The tyrosine kinase Yes1 is a druggable host factor of HEV - Haase, Jil Alexandra; Baheerathan, Abarna; Zhang, Xin; Fu, Rebecca Menhua; Nocke, Maximilian Klaus; Decker, Charlotte; Dao Thi, Viet Loan; Todt, Daniel; Neyts, Johan; Kaptein, Suzanne J.F.; Steinmann, Eike; Kinast, Volker (Hepatology Communications, 2024)
Background: HEV is a positive-sense, single-stranded RNA virus of the Hepeviridae family. Although HEV accounts for more than 3 million symptomatic cases of viral hepatitis per year, specific anti-HEV therapy and knowledge about HEV pathogenesis are scarce. Methods: To gain a deeper understanding of the HEV infectious cycle and guide the development of novel antiviral strategies, we here used an RNAi mini screen targeting a selection of kinases, including mitogen-activated protein kinases, receptor tyrosine kinases, and Src-family kinases. Further, we used state-of-the-art HEV infection models, including primary human hepatocytes and athymic nude rats. Results: Upon knockdown of the Src-family kinase Yes1, a significant reduction of HEV susceptibility could be observed, suggesting an important role of Yes1 in the HEV infectious cycle. Selective inhibition of Yes1 kinase activity resulted in significant inhibition of HEV infection in hepatoma cells and primary human hepatocytes, as well as in a rat HEV in vivo model system. Subsequent analysis of Y1KI during the HEV infectious life cycle indicated a role of Yes1 kinase activity in the early onset of HEV infection. Conclusions: We identified the dependence of HEV on Yes1 signaling, which may contribute to the so far scarce knowledge of HEV's pathogenesis in the future. Moreover, we provide Y1KI as a novel antiviral drug candidate specifically targeting an HEV host factor.
CRIS-Team Scopus Importer:2024-11-15
Keywords: antivirals; c-Yes; HEV; host factor; life cycle; viral entry; viral pathogenesis; Yes1